Biobutanol Production from Palm Kernel Cake (PKC) using Clostridium saccharoperbutylacetonicum N1-4 in Batch Culture Fermentation - Shukor, H; Al-Shorgani, NKN; Abdeshahian, P; Hamid, AA; Anuar, N; Rahman, NA; Isa, MHM; Kalil, MS (North Carolina State Univ Dept Wood & Paper Sci, 2024)
Indexed by WOS/ Scopus